How Many and Which Women Own Land in India? Inter-gender and Intra-gender Gaps. - Agarwal, Bina; Anthwal, Pervesh; Mahesh, Malvika (Journal of Development Studies, 2021)
Measuring gender inequality in land ownership is essential for assessing progress in women's economic empowerment, tracing the impact of progressive laws on actual practice, and monitoring SDG 5 on gender equality. To effectively assess inter-gender (male-female) gaps in land ownership, however, requires multiple measures. We also need to know which women are more likely to own land by tracing intra-gender differences. To date, no study on India has provided a full range of measures on inter-gender inequality in land ownership or focused on intra-gender variations. This paper uses unique longitudinal data to measure inter-gender gaps in agricultural land ownership through multiple indicators, and changes over 2009–2014 across nine states. It also analyses intra-gender gaps, and identifies the factors–individual, household and regional–affecting a woman's likelihood of owning land. Despite significant advancement towards equality in inheritance laws, women are found to constitute barely 14% of landowners owning 11% of agricultural land in rural landowning households, averaged across states. Moreover, women are significantly more likely to inherit land as widows than as daughters, highlighting the divergence between the legal strengthening of daughters' rights and the social legitimacy that widows' claims continue to enjoy over daughters' claims.